Novel Approach for the Characterization of Lewis Acidic Solid Catalysts by Solid‐State NMR Spectroscopy. Issue 12 (24th May 2016) - Lang, Swen; Benz, Michael; Obenaus, Utz; Himmelmann, Robin; Hunger, Michael
Abstract: Acetone‐2‐ 13 C, trimethylphosphine oxide (TMPO), and ammonia were applied as probe molecules for solid‐state NMR investigations of Lewis acid sites on γ‐Al2 O3, TiO2 /anatase, and lithium‐exchanged zeolite Na‐Y. An indication for Lewis acid sites are the 31 P MAS NMR signals at 48–51 ppm for TMPO‐loaded catalysts. The determination of the Lewis site density through the evaluation of these 31 P MAS NMR signals, however, is difficult owing to the demanding TMPO adsorption procedure. Upon ammonia adsorption, the formation of ammonium ions at Brønsted acid sites and the coordination of ammonia at Lewis acid sites cause 1 H MAS NMR signals at 6–7 ppm and −0.5–3 ppm, respectively. The integration of these signals results in the densities of Brønsted and Lewis acid sites. Future studies have to clarify whether the different 1 H chemical shifts in the range of −0.5–3 ppm for ammonia coordinated at Lewis acid sites on solid catalysts are a hint at the different strengths of these surface sites. Abstract : NMR characterization of Lewis acid sites : Lewis acid sites on TiO2, γ‐Al2 O3, and lithium‐exchanged zeolite Y were studied. 31 P MAS NMR spectroscopy of the trimethylphosphine oxide‐loaded catalysts allowed the identification of Lewis acid sites from the signals at 48–51 ppm. The site densities were determined by 1 H MAS NMR spectroscopy of the ammonia‐loaded catalysts and evaluation of the signals at −0.5–3 ppm.